Exergy analysis of organic rankine cycle and electric turbo compounding for waste heat recovery - Mat Muhammad, Mohd Hanif; Mamat, Aman Mohd Ihsan; Wan Salim, Wan Saiful-Islam (Science Publishing Corporation, 2018)
With such tough legislation on current emission standards, car manufacturers are focusing on increasing the efficiency of their engines with the development of advance waste heat recover (WHR) technology. Organic Rankine Cycle (ORC) and Electric Turbo Compound-ing (ETC) system have a good potential to be used as exhaust energy recovery. This paper compares the exergy availability and losses between the ORC and the ETC. In this particular study, exhaust data from the Proton 1.6L CamPro CFE turbocharged engine was used. This particular engine already has a main turbocharger, making the added WHR as a secondary recovery system to further increase the engine efficiency. Both systems are coupled to a 1 kW electric generator for ease of comparisons. At first the available exergy is calcu-lated for both WHR technologies. Exergy losses from rotating the generator are analysed to finally determine the thermal efficiency of the overall system. Exergy calculation is simplified to only account for chemical and physical exergy since kinetic and potential energy are negligible in comparison. Available exergy for ORC was significantly high which went up to 12.5 kW with the exergy losses record-ed at 9.7 kW. The ETC achieved only 5 kW but had a small loss at 8x10-3 kW. Average thermal efficiency of the ORC systems was 10.7% compared to ETC which was 58.7%. It can be concluded that the complexity of the ORC system contributes to its downfall where mul-tiple components increase its exergy losses compared to the simplistic design of an ETC.